Mechanisms underlying vasorelaxation induced in the porcine coronary arteries by Thymus linearis, Benth. (28th October 2018) - Alamgeer,; Auger, C.; Chabert, P.; Lugnier, C.; Mushtaq, M.N.; Schini-Kerth, V.B.
Abstract: Ethnopharmacological relevance: Thymus linearis, Benth indigenous to Pakistan has been traditionally used for the treatment of various diseases including hypertension. Aim of the study: Present study aims to investigate vasorelaxant effect of Thymus linearis and its underlying vasorelaxation mechanisms in porcine coronary artery rings. Materials and methods: Aqueous-methanolic extract of aerial parts of Thymus linearis was prepared by maceration process and then bio-guided fractionation was carried out using different solvents. The effects of extract and subsequent fractions were assessed on coronary artery rings with intact and denuded endothelium. The mechanisms of vasorelaxant effect were investigated using different pharmacological tools. The in-vitro inhibitory effects of the test fractions were also assessed on purified phophodiestrases using radioenzymatic assay. Phytochemical studies were carried out using GCMS. Results: The aqueous-methanolic extract elicited similar relaxations in coronary artery rings with and without endothelium in dose dependent fashion and removal of endothelium did not alter this response. Further, n-butanolic fraction of Thymus liniaris (TLB) was found to be the most potent among other derived fractions. TLB did not alter the relaxation produced by endothelium dependent vasodilators in rings with intact endothelium. However, TLB significantly potentiated the relaxation elicited by cyclic AMP and cyclic GMP elevating drugs but not those to soluble guanylyl cyclase activators (YC-1 and BAY 41–2272) and K + channel openers (levcromakalim and 1-EBIO). Pretreatment with TLB inhibited in a concentration-dependent manner contractions to KCl, CaCl2 and U46619 in coronary artery rings without endothelium. Further, TLB was found to non-selectively inhibit the PDE activity in concentration manner. Conclusion: n -Butanolic fraction of Thymus linearis possesses endothelium independent vasorelaxant effects in coronary artery by direct acting on the smooth muscles. These effects involve the elevation of the cyclic AMP and cyclic GMP possibly through the inhibition of various PDEs. GCMS analysis revel presence of thymole and carvacrol as major constituents. Furthermore, these investigations also support the folklore use of Thymus linearis in hypertension. Graphical abstract: